Identification of Plasmodium berghei Oocyst Rupture Protein 2 (ORP2) domains involved in sporozoite egress from the oocyst. Issue 14 (December 2018) - Siden-Kiamos, Inga; Pace, Tomasino; Klonizakis, Antonios; Nardini, Marco; Garcia, Celia R.S.; Currà, Chiara
Graphical abstract: Highlights: A portion of Plasmodium berghei ORP2 which is important for oocyst rupture was identified. The histone-fold domain interaction has a role outside transcription. Specific protein domains may play roles in sporozoite invasion. Abstract: Sporozoites are the infective form of malaria parasites which are transmitted from the mosquito salivary glands to a new host in a mosquito blood meal. The sporozoites develop inside the sporogonic oocyst and it is crucial for the continuation of the life cycle that the oocyst ruptures to release sporozoites. We recently described two Plasmodium Oocyst Rupture Proteins (ORP1 and ORP2), localized at the oocyst capsule, that are each essential for rupture of the oocysts. Both ORPs contain a histone fold domain implicated in the mechanism of oocyst rupture, possibly through the formation of a heterodimer between the two histone fold domains. To gain an understanding of the function of the different regions of the ORP2 protein, we generated deletion mutants. We monitored oocyst formation and rupture as well as sporozoites in the salivary gland. Our results show that different regions of ORP2 play independent roles in sporozoite egress. Deleting the N-terminal histone fold domain of ORP2 blocked sporozoite egress from the oocyst. Progressive deletions from the C-terminal resulted in no or significantly impaired sporozoite egress.